2006
DOI: 10.5194/angeo-24-1887-2006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of night-time absorption spike events

Abstract: Abstract. Sudden increases in cosmic radio noise absorption, known as spike events, have been identified as signatures of substorms in the previous studies. Using data from the IRIS (Imaging Riometer for Ionospheric Studies) at Kilpisjärvi, Finland (L ∼6) more than 450 night-time spike events between 1994 and 2003 have been identified. Spike events fall into four distinct categories based on their structure and the background magnetic activity as indicated by a local westward electrojet (IL index) derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…The resulting distribution of spikes is centered around the −2 hours MLT. A similar statistical result was also obtained by Aminaei et al [2006]. The comparison with the in situ electron injection distribution given by Thomsen et al [2001] yielded a puzzling difference: the peak of the in situ electron injection is displaced by about 3 hours MLT from that of the riometer spikes.…”
Section: Riometer Signatures Of Substorm Electron Injectionsupporting
confidence: 76%
“…The resulting distribution of spikes is centered around the −2 hours MLT. A similar statistical result was also obtained by Aminaei et al [2006]. The comparison with the in situ electron injection distribution given by Thomsen et al [2001] yielded a puzzling difference: the peak of the in situ electron injection is displaced by about 3 hours MLT from that of the riometer spikes.…”
Section: Riometer Signatures Of Substorm Electron Injectionsupporting
confidence: 76%
“…defined by solar radiation only) has been found to vary up to an order of magnitude between solar minimum and maximum (Kirkwood, 1993). Aminaei et al (2006) have showed that occurrence rate and amplitude of spikes in riometer data, which are associated with auroral particle precipitation, change by 14% and 1 dB, respectively, from solar minimum to solar maximum. Because the diurnal curves in Fig.…”
Section: Diurnal Pmse Variationsmentioning
confidence: 97%
“…The spike event also displays fine structure similar to magnetic Pi pulsations suggesting a common source region for the modulation (e.g. Hargreaves et al, 2001;Aminaei et al, 2006).…”
Section: Introductionmentioning
confidence: 96%